Acupressure: An Effective and Feasible Alternative Treatment for Anxiety During the COVID-19 Pandemic - Juan Yang MD, PhD; Alex Do L.Ac; Molly J Mallory L.Ac; Dietlind L Wahner-Roedler MD; Tony Y Chon MD; Brent A Bauer MD (SAGE Publishing, 2021)
Anxiety is highly reported during the COVID-19 pandemic. The use of acupressure for anxiety is a common practice in integrative medicine, and previous literature has shown that acupressure can be an effective and feasible alternative treatment for decreasing anxiety. Given the social distancing requirements during the COVID-19 pandemic, it appears reasonable to assume that acupressure may be especially suited to treat anxiety under these circumstances. However, there has been relatively little reported use of acupressure for anxiety during the pandemic. This viewpoint aims to highlight the possible role of acupressure as a self-administered therapeutic approach for anxiety amidst the COVID-19 pandemic and to outline key areas for future research.